2013
DOI: 10.1128/mbio.00535-12
|View full text |Cite
|
Sign up to set email alerts
|

Pilus Adhesin RrgA Interacts with Complement Receptor 3, Thereby Affecting Macrophage Function and Systemic Pneumococcal Disease

Abstract: Pneumococcal pili have been shown to influence pneumococcal colonization, disease development, and the inflammatory response in mice. The role of the pilus-associated RrgA adhesin in pneumococcal interactions with murine and human macrophages was investigated. Expression of pili with RrgA enhanced the uptake of pneumococci by murine and human macrophages that was abolished by antibodies to complement receptor 3 (CR3) and not seen in CR3-deficient macrophages. Recombinant RrgA, but not pilus subunit RrgC, promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
42
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(42 citation statements)
references
References 39 publications
0
42
0
Order By: Relevance
“…It is widely accepted that LPS from Gram-negative bacteria is recognized by TLR4 (44) and that peptidoglycan, teichoic acid, and lipoprotein are recognized by TLR2 (45)(46)(47). In the context of Streptococcus pneumoniae, some virulence proteins (RrgA pneumococcal pilus type 1 protein, GHIP, et al) bind to TLR2 (48,49) and Ply binds to TLR4 (50). Our results demonstrated that PepO-induced miR-155 upregulation relied on TLR2.…”
Section: Discussionmentioning
confidence: 54%
“…It is widely accepted that LPS from Gram-negative bacteria is recognized by TLR4 (44) and that peptidoglycan, teichoic acid, and lipoprotein are recognized by TLR2 (45)(46)(47). In the context of Streptococcus pneumoniae, some virulence proteins (RrgA pneumococcal pilus type 1 protein, GHIP, et al) bind to TLR2 (48,49) and Ply binds to TLR4 (50). Our results demonstrated that PepO-induced miR-155 upregulation relied on TLR2.…”
Section: Discussionmentioning
confidence: 54%
“…CR3 is a receptor present on the surface of most immune cells, including monocytes/macrophages, DCs, neutrophils, and natural killer (NK) cells, and plays an essential role in different immunological processes, including cell activation, chemotaxis, cytotoxicity, and phagocytosis (60) and tolerance induction (61). Previous studies demonstrated that pilus-associated adhesin RrgA from S. pneumoniae binds to CR3 and promotes bacterial uptake by murine and human macrophages (24). Using a similar approach with the same anti-CD11b antibodies, our data show that SpaCBA pili of L. rhamnosus GG promote bacterial phagocytosis by RAW 264.7 cells partially through CR3.…”
Section: Discussionmentioning
confidence: 99%
“…However, a possible immunomodulatory role of the native pili present on the surface of live L. rhamnosus GG has not yet been explored. Interestingly, in the case of the pathogen Streptococcus pneumoniae, interaction of the pilus-associated RrgA adhesin with the complement receptor 3 (CR3), also named integrin CD11b/CD18 or Mac-1, was shown to enhance uptake of the bacteria by murine and human macrophages, on the basis of the results of experiments with a blocking antibody on the wild type and the isogenic mutant lacking RrgA (24). In addition, TLR2 was shown to mediate inflammatory responses to oligomerized RrgA (25).…”
mentioning
confidence: 99%
“…Other pathogens such Bacillus anthracis (31), pneumococcus (32), and gonococcus (33) bind to Mac-1 to promote internalization of the bacterium or spore by the host cell. Both the pneumococcal pilus adhesion protein RrgA and the gonococcal porin and pili interact with Mac-1, like LukAB, via the I domain of CD11b (32,33).…”
Section: Discussionmentioning
confidence: 99%